Mitigating the Digital Age Impact: Collaborative Strategies of State and Religious Institutions for Family Harmony in Indonesia - Nurjanah, Siti; Ferliadi, Agus Salim; Jafar, Wahyu Abdul; Firdaus, Wihda Yanuar; Hamamah, Fatin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This research investigates the impact of information technology on family harmony in Indonesia, highlighting the increasing challenges for families characterized by rising divorce rates, domestic violence, and juvenile delinquency, exacerbated by social media, which is a form of information technology development. Through qualitative analysis using field research methods, this study reveals the urgent need for protective measures to safeguard families and children in the digital age. The results show a separate role for religious and state institutions in mitigating the impact of technological development. The research, therefore, emphasizes the importance of a collaborative role between state and religious institutions in mitigating these negative impacts by implementing comprehensive strategies that promote family education, strengthen moral values, and increase parental involvement. The findings advocate for solid policies and proactive institutional engagement to foster a supportive environment for families, ultimately aiming to cultivate a harmonious society amidst the complexities brought about by technological advancements.